Transformasi Politik Islam Di Turki Pada Era Erdogan Dalam Perspektif Fiqh Siyasah - Gilang Maulana; Mustafa Al Ghifari; Rafif Putra Ananda; Ihsan Maulana Syahputra; Syabti Syahputra Pohan (Tabayyun : Journal Of Islamic Studies, 2026)
This study examines the transformation of Islamic politics in Turkey during the leadership of Recep Tayyip Erdogan through the perspective of fiqh siyasah, particularly the political thought of Al-Mawardi in Al-Ahkam al-Sultaniyyah. The research is motivated by the significant shift in Turkey’s political orientation from strict secularism toward a more accommodative approach to Islamic values within a modern democratic framework. Previous studies have predominantly focused on democratization, Islamic political movements, and Turkey’s foreign policy, while limited attention has been given to evaluating Erdogan’s leadership using the normative framework of classical Islamic political thought. This research employs a qualitative library research method with a normative-analytical approach. Data were collected from classical and contemporary literature related to fiqh siyasah, Turkish political developments, and the political thought of Al-Mawardi. The findings reveal that the political transformation under Erdogan represents a hybridization between Islamic identity and modern democratic governance. From the perspective of fiqh siyasah, Erdogan’s leadership demonstrates conformity with the principles of al-kifayah (leadership capacity), hifz al-din (protection of religion), and maslahah (public welfare), particularly through political stability, economic development, and the strengthening of religious identity in the public sphere. However, challenges remain regarding the implementation of al-'adalah (justice), especially in relation to civil liberties, political opposition, and the concentration of executive power following the 2017 constitutional referendum. Furthermore, the analysis based on maqāṣid al-syarī‘ah indicates that political legitimacy in Islam should not merely be assessed through symbolic religious policies but also through the realization of justice, public welfare, and the protection of fundamental rights. Therefore, the Turkish experience under Erdogan illustrates an adaptive reinterpretation of classical Islamic political principles within the realities of a modern nation-state.